Technological advancement, sectoral growth, and electricity consumption in Ghana. (15th January 2023) - Amoako, Samuel; Andoh, Francis Kwaw; Asmah, Emmanuel Ekow
Abstract: As part of measures to ensure the adoption and application of energy-efficient systems, Ghana has rolled out some policies and programmes (namely the Technology Transfer Regulation, 1992 (LI 1547), Technology and Innovation (STI) and the Meltwater Entrepreneurial School of Technology (MEST)). There has also been dynamics sectoral growth and contribution to national output. However, empirical assessment of the cumulative effects these technologically induced policies and programmes, as well as the sectors as on energy use is missing in the literature. This study uses annual data from 1984 to 2014 to assess how the push for technological advancement and sectoral growth, has impacted electricity consumption using the Ordinary Least Squares (OLS), the Fully Modified Ordinary Least Squares (FMOLS) and the Canonical Cointegration (CCR). The results suggest that technology exhibits a linear and negative relationship with electricity consumption. Secondly, growth in the Services and Industry sectors, positively corelates with electricity consumption, implying energy inefficiency. The adoption of energy efficient systems at the sectoral level as well as a robust structure of monitoring and evaluation of technological trends as relates to electricity consumption is recommended. Highlights: Study examines how specific policies aid in energy efficient technology use. High commercial energy consumption may correlate positively with high GDP. Negative relationship between technological advancement and electricity use. Sectoral policies unique to each sector's demand on energy efficiency is advised.